Transcranial magnetic stimulation for the treatment of chronic low back pain: a narrative review - Olechowski, Camille; Gener, Maricar; Aiyer, Rohit; Mischel, Nicholas (Frontiers in Pain Research, 2023)
Background Chronic low back pain is a debilitating condition that impacts millions of individuals around the world, and also has an enormous economic impact. The impact of chronic pain does not only involve physical health, but can also play a detrimental role in a patient's mental health. Consequently, it is critical to approach these patients with multimodal management. Initially, a treatment plan which includes medications, psychotherapy, physical therapy, and invasive interventions can be utilized for chronic back pain. However, many patients experience refractory low back pain to these initial treatments, which can result in non-resolving chronic pain. As a result, many new interventions have been developed in recent years to treat refractory low back pain, including non-invasive transcranial magnetic stimulation. In recent years, there has been some limited and preliminary evidence for the treatment of chronic low back pain with transcranial magnetic stimulation, as further investigation on this intervention is warranted. After reviewing analytically high impact studies, our objective is to provide a narrative review of the treatment of chronic low back pain with repetitive transcranial magnetic stimulation (rTMS). Methods We performed a comprehensive database search on PubMed, Embase, PsychInfo, Web of Science, and CINAHL for literature that pertains to the treatment of chronic low back pain with transcranial magnetic stimulation using these terms: “Chronic Low Back Pain and Transcranial Magnetic Stimulation”, “Low Back Pain and Transcranial Magnetic Stimulation”, “Chronic Back Pain and Transcranial Magnetic Stimulation”, “Chronic Low Back Pain and TMS”, “Low Back Pain and TMS”, and “Chronic Back Pain and TMS”. We aim to provide a narrative review of the role of rTMS in CLBP. Results Initial search results from September to November 2021 using the above-mentioned search criteria included 458 articles, of which 164 duplicates were removed and 280 were further excluded by a three-person (CO, NM and RA) screening process. Articles were further filtered based on various exclusion and inclusion criteria. The resulting 6 studies are discussed. Discussion The studies reviewed suggest the potential benefit in chronic lower back pain symptoms after various rTMS protocols and sites of stimulation. However, the included studies are not without issues in design for example: not randomized, not blinded, or have small sample size. This review highlights the need for scaled, better controlled research studies and standardization of treatment protocols to determine if rTMS for chronic lower back pain will be accepted as a standard treatment option for patients with chronic lower back pain symptoms.